Influence of asphalt cement type and oven type on asphalt retention capacity of paving geotextiles. Issue 2 (April 2006) - Castro, D.; Ballester, F.
Abstract : This paper presents results from asphalt retention tests on geotextile products carried out in accordance withASTM D 6140 . Three different geotextile products were used in combination with three different asphalt cements and two different types of oven (convection and forced air types). The results show important variations in retention values depending on the asphalt cement and the oven used. The current ASTM standard recommends using a convection oven. If the tests are carried out using a forced air oven, significantly lower values of asphalt retention capacity can be expected.